The Sustainable Tourism Implementation in Bonjeruk Tourism Village, Central Lombok - Sumardani, Rizki; Wiramatika, I Gede (Jurnal Manajemen Pelayanan Hotel, 2023)
Sustainable tourism is to improve the welfare, economy, and public health. Improving the quality of life canonly be achieved by minimizing the negative impacts of non-renewable natural resources, the aims of theresearch are (1) to find out the application of the principles of sustainable tourism (2) to identify the impact ofthe implementation of sustainable tourism on the environmental, economic and socio-cultural dimensionscommunity of Bonjeruk Tourism Village, the location of the research was conducted in Bonjeruk TourismVillage, Central Lombok Regency, the method used was descriptive qualitative with data collection techniquesof interviews, observation, documentation, and literature study, the type of data in this study was primary andsecondary data, techniques data analysis in research was carried out by data reduction, data presentation, andconcluding. The results in this study indicate that the implementation of sustainable tourism in the BonjerukTourism Village is carried out jointly between the community and the local management to realizeenvironmentally friendly tourism, preserve the surrounding environment and foster a sense of care for thesurrounding community to always maintain clean, beautiful environmental conditions. safe and comfortablefor tourists and the surrounding community, the impact of implementing sustainable tourism onenvironmental conditions, namely the community and managers of each house have trash bins, economicallythe community gets work or income from the Bonjeruk Tourism Village and from a social perspective thecommunity can preserve art and culture by regenerating youth in Bonjeruk Tourism Village.Keywords: Sustainable Tourism, Bonjeruk Tourism Village